The Effectiveness of Lavender Aromatherapy on Pain Scores for Post Sectio Caesarea in The Puskesmas Sukahaji Majalengka Regency - Agustina Risvianti, Eka; Mutya Sari, Vianty; Widayanti, Wiwin; Rizki Nurfita, Nisa (Ann Publisher, 2023)
Sectio Caesarea (SC) deliveries have a higher risk because the surgery is performed by opening the abdominal wall and uterine wall or a trans-abdominal incision of the uterus. Patients with SC will feel pain. Therefore, pain management will be more effective when combined with non-pharmacological therapy. One of the non-pharmacological therapies that can be applied is aromatherapy. The purpose of this study was to determine the effectiveness of lavender aromatherapy on the pain score of post sc in the area of Puskesmas Sukahaji Kab Majalengka Tahun 2023. The design used is a quasi-experimental with one shoot only, the number of samples is 15 intervention groups and 15 control groups, the sampling technique uses purposive sampling. The results of data analysis obtained an average value in the intervention group of 2.60 and the control group of 7.33. The results of the Mann Whitney test. Research result obtained a value of p = 0.000 or p <0.05 meaning that lavender aromatherapy is effective against post SC maternal pain scores. Lavender aromatherapy is effective for post SC maternal pain scores in the Sukahaji Health Center area in 2023. It is hoped that it can be used as a complementary therapy in pain management so that it becomes a holistic and comprehensive treatment therapy